Ultrasonic and Microwave-assisted Solid-Liquid Extraction of Ginkgo biloba Phenolics: Study about Mass Transfer and PID Control - Chi XU; Hebin XU; Rui ZHU; Jing LI; Dandan LI; Yongbin HAN; Yi ZHENG; Yang TAO (Shipin gongye ke-ji)
In this study, both ultrasound and microwave techniques were utilized to intensify the extraction of phenolics from Ginkgo biloba leaves. A diffusion-based mathematical model was developed to explore the mass transfer mechanism about the studied extraction processes, and PID control algorithms were implemented to accurately control the extraction process. The results showed that ultrasound and microwave-assisted methods significantly enhanced the release and diffusion of polyphenol compared to the traditional shaker oscillation method. Compared with ultrasound-assisted extraction, microwave-assisted extraction demonstrated superior efficiency and diffusion effectiveness, quickly reached the maximum polyphenol content gradient across the leaf particles. With a solvent-to-liquid ratio of 1:40 g/mL, the effective diffusion coefficient (De) of polyphenol was determined to be 6.4×10−11 m2/s under ultrasound treatment (103.7 W/L) and ranged from 1.4×10−10 to 1.7×10−10 m2/s under microwave treatment (4800 W/L). The equilibrium polyphenol extraction yields were 27.492±2.666 mg/g for ultrasound treatment at 103.7 W/L and 28.453±1.115 mg/g for microwave treatment at 4800 W/L. Furthermore, fuzzy-PID controllers optimized by genetic algorithms or particle swarm optimization (PSO) algorithms outperformed traditional PID controller and individual fuzzy-PID controller to control the extraction process, achieving faster convergence with minimal overshoot. Specifically, under microwave power of 4800 W/L and a solvent-to-liquid ratio of 1:20 g/mL, the fuzzy-PID controller optimized by PSO algorithm proved optimal, with PSO factors set at 4.1350, 0.1100, and 0.0001. The corresponding convergence time was approximately 0.5 minutes and an overshoot was 1.12%. This study provides a theoretical foundation for digitalizing the ultrasonic and microwave-assisted extraction processes of polyphenol from Ginkgo biloba leaves.